Implementation of Problem Based Learning (PBL) Type Model in Science Subject to Improve Learning Outcomes of V Grade Students SD NU Metro - Rika Nadiyanti; Masrurotul Mahmudah; Lutfi Fadilah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
This study aims to determine how teachers apply the problem based learning model to improve the learning outcomes of fifth grade students and how to improve the learning outcomes of fifth grade students of SD NU Metro. In this study, the problem based learning model. This study uses qualitative with an inductive thinking process to understand reality. Data collected through observation, interviews with the principal, teachers and students and documentation. The results of this study indicate that this problem based learning model is very effective in improving student learning outcomes, student involvement in learning, student understanding in solving problems, developing student skills to think critically. In addition, the problem based learning model also creates active and enjoyable learning. Thus, this problem-based learning model can continue to be developed for learning that can improve student learning outcomes at SD NU.